Pulmonary and biceps function after intercostal and phrenic nerve transfer for brachial plexus injuries - Chalidapong P. (2014)
This pseudo-randomized study was performed to compare the pulmonary function and biceps recovery after intercostal (19 cases) and phrenic (17 cases) nerve transfer to the musculocutaneous nerve for brachial plexus injury patients with nerve root avulsions. Pulmonary function was assessed pre-operatively and postoperatively by measuring the forced vital capacity, forced expiratory volume in 1 second, vital capacity, and tidal volume. Motor recovery of biceps was serially recorded. Our results revealed that pulmonary function in the phrenic nerve transfer group was still significantly reduced 1 year after surgery. In the intercostal nerve transfer group, pulmonary function was normal after 3 months. Motor recovery of biceps in the intercostal nerve group was significantly earlier than that in phrenic nerve group. We conclude that pulmonary and biceps functions are better after intercostal nerve transfer than after phrenic nerve transfer in the short term at least.